Rare-earth doped radioluminescent hydrogel as a potential phantom material for 3D gel dosimeter - Yang Tao (De Gruyter, 2021)
Cancer prevention and treatment are currently the focus of most research. Dose verification is an important step for reducing the improper dose deposition during radiotherapy. To mend the traditional gel dosimeters for 3D dose verification, a novel rare-earth nanoparticle-based composite gel was prepared, which has good radioluminescence property and reusability. It is a promising phantom material for the new 3D gel dosimeter. TEM, DLS, FT-IR, TGA, and spectrofluorometer were used to determine the chemical structure, micromorphology, and optical performance. Compared to the traditional gel dosimeters, the composite gel has a good linear relationship between the light intensity excited by X-ray and the tube current. Furthermore, it may measure the dose distribution immediately in situ, which reduces errors and saves time. This work provides a new idea for the research of 3D gel dosimeters and promotes the safe and effective use of radiotherapy.